Occupational triphenyltin acetate poisoning: a case report. Issue 2 (February 1991) - Colosio, C; Tomasini, M; Cairoli, S; Foà, V; Minoia, C; Marinovich, M; Galli, C L
Abstract : A case of triphenyltin acetate (TPTA) poisoning is described. The patient, who had been exposed mainly to cutaneous absorption, showed acute stages of an urticarial eruption, signs of hepatic injury, slight glucose intolerance, and electroencephalographic abnormalities. Concomitant with the highest concentrations of tin in plasma and the peak of tin excretion in urine, neutrophils did not show the normal increase in actin polymerisation after stimulation with a chemotactic peptide (100 nM fMLP). The peak of urinary excretion of tin occurred between the fifth and the sixth day after poisoning; subsequently, the rate of excretion became slow, suggesting biphasic kinetics with the possibility of a cumulative trend.